Post-traumatic descending aorta intramural haematoma fortuitously witnessed during a magnetic resonance examination of the spine - Cademartiri, F.; Salamousas, B.V.; Luccichenti, et al., G. (Acta Biomedica Atenei Parmensis, 2004)
Most patients with traumatic aortic lesions of the thoracic aorta die at the accident site but 15% arrive at the hospital with vital signs. Digital subtraction angiography is considered the gold standard for the diagnosis of traumatic lesions of the thoracic aorta. Other non-invasive diagnostic techniques, such magnetic resonance and spiral computed tomography, proved to be reliable alternatives. Sometimes the diagnosis can be delayed by the relative lack of significant symptoms as well as the presence of unusual clinical findings. A case of post-traumatic intramural haematoma of the descending aorta revealed during a magnetic resonance of the spine is described. The final diagnosis was obtained with spiral computed tomography.